ETP/GDOP behavior study for N-sensors arrays in a multilateration radar system - Mantilla-Gaviria, Iván Antonio; M. Sc. Tech., Systems and CommunicationNetworks Researcher - ITACA Research Institute, Applied Electromagnetism Group Polytechnic University of Valencia Valencia (Universidad Santo Tomás. Seccional Bucaramanga, 2009)
In this paper, we evaluated the ETP (Expected Theoretical Precision) and GDOP (Geometric Dilution Of Precision) enhancement related to the number of sensors in a Multilateration radar system. An introduction about the principles of the Multilateration radar system basis operation is described, then, the formulation for evaluation the ETP/GDOP of the 3D positioning is shown. We observed that the ETP and GDOP enhance with the increase of the number of sensors. A substantial improvement was obtained until nine sensors but, for more sensors that improvement is reduced. Results for a 75km×75km area are shown, including LAM (Local Area Multilateration) and WAM (Wide Area Multilateration) settings and different values of the aircraft height (5m for LAM surface, 5000m and 8000m for WAM). Additional parameters are shown in order to evaluate the system quality. These parameters are the Expected Theoretical Precision Gain (ETP Gain), Homogenization Level (HL) and Percentage Over a Reference Value (PORV). Due to the proportionality between the ETP and GDOP, only ETP results are shown. In the simulations the same settings of the sensors was used; 3ns for instrumental error and 27m for antenna height. These are typically values for real Multilateration radar system used for the air traffic control.